Analisis Semiotika Komparatif Gaya Komunikasi Kepemimpinan Michael Corleone Dalam Film The GodFather Part II Dan Citra Politik Prabowo Subianto - Muhammad Rizky Nugroho Saputro; Arian Alfraita; Fitria Widiyani Roosinda (CV. ITTC INDONESIA, 2026)
This study analyzes the comparative leadership communication style of Michael Corleone in the film The Godfather Part II and the political image of Prabowo Subianto using Roland Barthes' semiotic theory. This study uses a descriptive qualitative approach, this study examines Michael Corleone's important scenes such as dialogue, body language, and visual elements which are then used as a comparison with Prabowo Subianto's political image. The research findings show that the signs in the film and Prabowo Subianto's political image operate at the denotative, connotative, and myth levels. At the denotative level, Michael's actions appear as ordinary communication in business and family relations, while Prabowo Subianto's leadership communication is more oriented towards creating public legitimacy and consolidating political power. At the connotative level, Michael's communication represents absolute power that works through psychological control, while Prabowo Subianto builds an image through a nationalistic approach and social closeness. At the myth level, Michael Corleone forms the myth of a strong, cold leader because he is able to control his emotions and keep his distance from others. Prabowo Subianto forms the myth of a strong leader but remains close to the community through open communication and symbols of social closeness.